Role of renal artery embolization in treatment of iatrogenic renal bleeding - Eman Shawky Geneidi,; Nivan Hany Khater,; Mostafa Farid,; Mohammed Sabry Abdo Attaallah alalfy, (Journal of the Pakistan Medical Association, 2023)
Objective: To review institutional experience about the effectiveness and safety of percutaneous trans-arterial renal artery embolization in the treatment of iatrogenic renal bleeding. Methods: The prospective study was conducted from December 2019 to December 2021 at Ain Shams University Hospital and Kafrelsheikh University Hospital, Egypt, and comprised patients of either gender who underwent renal artery embolization for iatrogenic arterial renal bleeding caused by percutaneous nephrolithotomy, renal biopsy and percutaneous nephrostomy. Diagnostic renal angiography was done to detect pseudoaneurysm and arteriovenous fistula. Embolization was done with either micro-coils or glue. Success of the procedure was defined as total occlusion of the bleeding artery proved by post-embolization angiogram. Results: Of the 15 patients, 9(60%) were males and 6(40%) were females. The overall mean age was 35+/-14 years. Percutaneous nephrolithotomy was the main cause 8(53.3%), followed by renal biopsy 5(33.3%) and percutaneous nephrostomy 2(13.2%). There were 9(50%) cases of pseudoaneurysm and 6(40%) of arteriovenous fistula. Embolization was done with micro-coils in 5(33.3%) cases and with glue in 10(66.6%). The technical success rate was 15(100%). No major complications requiring intensive care or surgical intervention were encountered, and there was no significant differences in estimated glomerular infiltration rate or renal function after renal artery embolization (p>0.05). Conclusions: Percutaneous endovascular renal artery embolization was found to be a safe and effective technique in the management of iatrogenic renal arterial injury. Keywords: Renal artery, Aneurysm, Nephrostomy, Percutaneous, Arteriovenous, Angiography.